2021
DOI: 10.1111/jbg.12638
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction in a numerically small breed population using prioritized genetic markers from whole‐genome sequence data

Abstract: The objective of this study was to investigate the accuracy of genomic prediction of body weight and eating quality traits in a numerically small sheep population (Dorper sheep). Prediction was based on a large multi-breed/admixed reference population and using (a) 50k or 500k single nucleotide polymorphism (SNP) genotypes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…These findings are in line with results from previous studies, demonstrating increased accuracy when information from genotypes is included, such as for Manech Tête Rousse dairy sheep (Macedo et al, 2020 ), small population of Dorper sheep (Moghaddar et al, 2022 ) or chicken mortality (Bermann et al, 2020 ). Furthermore, several studies comparing accuracies obtained from various genomic models indicate single‐step BLUP as the best way for getting high accuracy values in sheep (Baloche et al, 2013 ) or dairy goats (Mucha, Bunger, & Conington, 2015 ; Mucha, Mrode, et al, 2015 ).…”
Section: Resultssupporting
confidence: 90%
“…These findings are in line with results from previous studies, demonstrating increased accuracy when information from genotypes is included, such as for Manech Tête Rousse dairy sheep (Macedo et al, 2020 ), small population of Dorper sheep (Moghaddar et al, 2022 ) or chicken mortality (Bermann et al, 2020 ). Furthermore, several studies comparing accuracies obtained from various genomic models indicate single‐step BLUP as the best way for getting high accuracy values in sheep (Baloche et al, 2013 ) or dairy goats (Mucha, Bunger, & Conington, 2015 ; Mucha, Mrode, et al, 2015 ).…”
Section: Resultssupporting
confidence: 90%
“…Other studies have found small but often unstable improvements (e.g., from 1 to 5% or no improvement depending on the prediction method used [17][18][19], or trait-dependent results [19,20]). For genomic prediction across populations, the identification and inclusion of causal variants from WGS have been shown to improve prediction accuracy [21][22][23][24], especially for numerically small populations and for populations that are not represented in the training set [21,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The design of biology‐informed custom SNP arrays may outperform the standard arrays, HD arrays and even WGS in terms of predicting genetic values (Brøndum et al, 2015; Moghaddar et al, 2022; Raymond et al, 2018; VanRaden et al, 2017; Xiang et al, 2021). A study by Brøndum et al (2015) showed that including 1623 QTL markers derived from WGS into a medium‐density chip increased prediction accuracies by 3–5 percentage points.…”
Section: Discussionmentioning
confidence: 99%
“…These variants can be identified through GWAS, gene expression studies, sequence data and other tools. This approach has been adopted and shown to be more accurate than WGS prediction in some scenarios (MacLeod et al, 2016; Moghaddar et al, 2022; Raymond et al, 2018). The limitation of including WGS data is likely due to the inclusion of a vast number of redundant SNPs with high LD (VanRaden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%